Inflation Centralized And Distributed Databases in Stores (Comprehensive Journal of Science, 2025)
use systems in shops is crucial for enhancing efficiency These systems manage salestransactions and include features such as inventory tracking, customer management, andsales reporting. These systems usually used Databases that organized collections data bythese systems in shops but with long working these systems for long years the size forthese database become bigger than when start work that makes the systems in shops workslowly and least efficiency their size refers to the amount of data stored within them, typicallymeasured in bytes, kilobytes (KB), megabytes (MB), gigabytes (GB), terabytes (TB), or evenlarger units like petabytes (PB) for large-scale systems.There are many Types of Databases such as MySQL, PostgreSQL, Oracle, Microsoft SQLServer. Size of database : Usually well-suited for small to medium-sized datasets but canscale to terabytes and beyond with proper indexing, partitioning, and optimization.With the continuous use of these systems in commercial stores and the increase inoperations on them, such as updating and deleting data and adding data to the database,their efficiency decreases and their slowness increases. This phenomenon is calleddatabase inflation or database bloat.